Violencias ovejunas en las misiones jesuíticas de guaraníes (Paraguay, siglos XVII-XVIII) - Thomas Brignon (E-Spania)
A singular evangelizing experience, the 30 Missions of the Guaraní, established by the Society of Jesus in Paraguay (1609-1768), have been depicted like a utopic Arcadia. The Jesuits would apply a pastoral ideology, treating the Indians as a human flock, as an alternative model to colonial violence. This article aims to establish the practical and concrete role of sheep herding in the Reductions’ daily life, through the analysis of local-use documents written in Guaraní. These texts reveal a gap between the weight achieved by pastoralism in missionary imagery and the marginal presence of sheep as living beings. Faced with a hostile environment, they were also victims of violence from the Guaraní themselves, who were aware of the functions these animals endorsed in Christian discourse and colonial rule.